COMPARISON OF TWO GROUP APPLICATION PROCEDURES DESIGNED TO INDUCE ANXIETY - Nuevo, Roberto; Cabrera, Isabel; Márquez-González, María; Montorio Cerrato, Ignacio (Anales de Psicología / Annals of Psychology, 2008)
Objective: The present work aims to comparatively analyze the effectiveness of the group application of two different procedures designed to induce anxiety. Method: Sixty two students of psychology were randomly assigned to one of the two following anxiety induction conditions, using a between-subjects design with repeated measures (pre-post induction). In the A condition, subjects were exposed to anxiogenic scenes of different films. In the B condition, they were asked to read selfreferential statements with threatening content and, after the reading, they listened to a piece of anxiogenic music. Results: In the A condition (Films), significant increases in nervousness and tension and decreases in the level of vigour and well-being were found, with effect sizes ranging between .50 and 1.45. For the B condition, pre-post differences were significant and in the same direction, although effect sizes were slightly lower (between .38 and .80). The change after the induction (pre-post differences) in both conditions in most DVs significantly correlated neither with the level of trait anxiety nor with a measure of social desirability; however, in the B condition, the change after the induction presented a significant association with a measure of suggestibility. Conclusions: The two procedures of anxiety induction analyzed in this work seem to be effective, although the effects seem to be stronger for the film condition, which is proposed as a tool for the experimental manipulation of the level of anxiety in younger adults in group application contexts.